The Role Of Risk Management In Enhancing Company Resilience - Robertus Maria Bambang Gunawan (Eduvest - Journal of Universal Studies, 2024)
In an era of globalization full of uncertainty, companies are faced with various risks that can disrupt the smooth running of operations and even threaten their sustainability. The aim of this research is to analyze the role of risk management in increasing company resilience. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the role of risk management in increasing company resilience is as a tool to identify, measure and manage potential risks that can have a negative impact on the company's strategic targets. Implementing risk management can help companies build resilience against risks that can disrupt operations, protect organizational assets, reduce losses, increase compliance with applicable regulations, laws or standards, and optimize opportunities. Implementing risk management can be done through several steps, such as risk identification, risk evaluation and risk management.